Preservation Technique of Dwarf Elephant Grass Cuttings (Pennisetum purpureum CV mott.) - Desy Valentina P; Nevy Diana Hanafi; Tri Hesti Wahyuni; Achmad Sadeli (Talenta Publisher, 2018)
The breeding of dwarf elephant grass generally uses vegetative methods, namely using cuttings. The constraints faced and the distribution of cuttings are the nature of which are easily damaged during storage due to physiological activities and invasion of microorganisms. This study aims to find a number of preservation techniques that can maintain the age and quality of dwarf elephant grass cuttings (Pennisetum purpureum cv mott.). This research was carried out in the Faculty of Agriculture Universitas Sumatera Utara, starts from July to August 2018. The design used is a 5 x 5 factorial complete randomized design (RAL), with 4 replications each consisting of 3 cuttings. The results showed that the general condition of the cuttings planting material was better until storage for 20 days, namely A4; the average shrinkage weight of the cuttings is significantly different in the A4 (refrigerator) treatment that is equal to 1.532 and the longer it is stored the higher the weight loss; the average power grows is significantly different in treatment A1 (wax) which is equal to 1.950 and the longer it is stored the lower the power to grow cuttings. The average vertical height is significantly different from the A1 treatment (wax) with a value of 10,585.